A FORENSIC PRAGMATIC ANALYSIS OF SUICIDE NOTES: A CASE STUDY OF A COUPLE IN MAKASSAR, INDONESIA - Muhammad Tahir; Andi Sahtiani Jahrir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study presents a forensic pragmatic analysis of two suicide notes written by a young couple in Makassar, Indonesia, who died by suicide in November 2023. Using a qualitative descriptive approach, the research applies the theories of implicature (Grice, 1975), presupposition (Levinson, 1983), and speech acts (Searle, 1979) to uncover implicit meanings and communicative intentions embedded within the notes. The data, consisting of handwritten texts publicly verified by authorities, were analyzed thematically to identify expressions of emotional exhaustion, perceived burden, and unresolved relational conflict. The findings reveal that both notes are rich in indirect language, culturally shaped presuppositions, and emotionally charged speech acts that function as both personal expressions and posthumous directives. Moreover, gendered linguistic patterns suggest differing emotional emphases and narrative tones between the two writers. The study highlights the role of language in encoding psychological distress and social obligations, offering new insights into the intersection of linguistics, mental health, and forensic inquiry. By focusing on suicide discourse in a Southeast Asian context, this research contributes to the underrepresented domain of non-Western forensic linguistics and emphasizes the value of pragmatic analysis for suicide prevention and legal interpretation